2018
DOI: 10.1002/ange.201800294
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Electron Conductance Regimes in Bacterial Decaheme Cytochromes

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
(109 reference statements)
2
14
0
Order By: Relevance
“…Electron flow from heme 10 or 5 to the side exits 7 and 2 is similarly fast as along the octaheme main chain, about 10 5 s −1 , except for 10 → 7 due to the relatively high reduction potential of heme 7. However, the latter is subject to uncertainty as discussed previously (26,27) and may be overestimated. The reverse flow from the side exit 7 or 2 to 10 and 5 is somewhat slower, typically about 10 4 s −1 , due to successive uphill steps involving coplanar and T-shaped motifs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Electron flow from heme 10 or 5 to the side exits 7 and 2 is similarly fast as along the octaheme main chain, about 10 5 s −1 , except for 10 → 7 due to the relatively high reduction potential of heme 7. However, the latter is subject to uncertainty as discussed previously (26,27) and may be overestimated. The reverse flow from the side exit 7 or 2 to 10 and 5 is somewhat slower, typically about 10 4 s −1 , due to successive uphill steps involving coplanar and T-shaped motifs.…”
Section: Resultsmentioning
confidence: 93%
“…This undertaking is very timely, because the crystal structure of MtrC has recently become available. While Barrozo et al (27) have recently presented a preliminary characterization of the ET kinetics for MtrC, although with outdated electronic couplings from MtrF, a full and up-to-date characterization for this protein is outstanding.…”
mentioning
confidence: 99%
“…In an early study, Breuer et al reported redox potentials for all 10 hemes in alloxidized MtrF using MD simulation, 25 and very recently Barrozo et al reported heme redox potentials for MtrF and MtrC in all-ox and all-red states. 31 Both studies agreed that the free energy profile for electron flow along the wire has ups and downs, yet resulting in near thermoneutral ET along the long axis of the protein (heme 5 to 10). In terms of kinetics, several ET mechanisms have been investigated including bandlike, 49 flickering resonance (FR), 28, 50 superexchange (SE) 28 and electron hopping.…”
Section: Electron Transfer Kineticsmentioning
confidence: 67%
“…These efforts may help us understand observed functional differences between the two proteins. 31 As always, computational predictions are subject to uncertainties (e.g. protonation state of the protein) and inaccuracies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation